Monitoramento energético em nuvens computacionais - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Computational clouds consume lots of electrical energy and are responsible for causing the issuance of 2% of globally carbon dioxide. Some cloud managers, such as OpenNebula, have no resources to monitor the energy consumption of their services and infrastructure, making the cloud administrator uninformed about the amount of electrical energy spent. Therefore, this work aims to create a system for monitoring energy consumption in data centers virtualized with Kernel-based Virtual Machine and managed by OpenNebula. The proposed system is called Monitor Energético (ME) and is divided in Monitor Energético em Bash (MEB) to collect virtual machines’ energy consumptions and Monitor Energético em Web (MEW) for display energy data at OpenNebula Web interface. Experiments performed with Sysbench tool proved the correctness of the proposed system during the purposeful stress of the analyzed environment.
Keywords: Computer science; Computer networks; Efficiency energy; Linux; OpenNebula; Ciência da computação; Redes de computadores; Eficiência energética; Linux; OpenNebula; CNPQ::CIENCIAS EXATAS E DA TERRA